Sosialisasi Moderasi Beragama di GMIT Zoar Penkase - Nofita Rudiani Asbanu; Saniria Benu; Neti Saekoko; Claudina Margarida Freitas Belo; Barbara Green Winsle Bessie; Ivony Welchristin Adelis Oematan; Salomi Poko; Harun Yeremia Natonis; Anita Adriance Hege Udju (Jurnal Pelayanan Masyarakat, 2025)
The Community Service (PKM) activity conducted by the Master's Program in Christian Religious Education at GMIT Zoar Penkase addressed the theme "Religious Moderation and Religion in Public Spaces." The primary objective of this activity was to enhance the understanding of the community and congregation regarding the importance of moderation in religion as a key to preventing conflicts and violence based on religious differences. This activity involved 27 participants, including students, lecturers, religious leaders, and local community members. The material presented emphasized the significance of moderate attitudes and respect for differences within the context of religious diversity. Issues of humanity, tolerance, and national commitment were discussed, with the hope of strengthening social cohesion. The results of this activity indicate that religious moderation can serve as a unifying force that promotes social justice and harmony among religious communities. Thus, religious moderation in public spaces is crucial for creating a more inclusive, peaceful, and just society, both locally and globally.